PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 038 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sepreni, Sepreni; Zulkifli, Zulkifli; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: Background in this research is the low learning outcomes grade IV SD 038 Sekeladi because the students are still less active in receiving lessons. The teacher is less engaging students in learning and teachers just use eneryption methods lecture and less involved directly students to determine their own and the knowledge that they are holding on of these problems need to be doing class action research (PTK) with the application of the cooperative learning model type numbered head togrther This research alms to improve the learning results of IPA grade IV SDN 038 Sekeladi with the number of students as many as 18 people students. This research was done with two cycles each cycle consists of two times meeting with one-time deateronomy daily unstrumen data collection in this research is the observation sheet and test the results of the study. The results of the data analysis cictivities teachers on the first I pertemuan cycle 50% and the second meeting was increased to 62,5% at the first meeting of the II cycle 82,5 % and the second meeting was increased to 92,5%. Further mor the results of the tada analysis of student activity on the cycle I the firstmeeting 50% and the second meeting was increased to 62,5 % at the first meeting of the II cycle 82,5% an the second meeting was increased to 92,5% from the results obtained in this research study results of student experience increased that is the average of the results of the study on base score is 6,50 increaset cycle I be 68,0 increased again in the cycle of II tht is 73,6 for ketuntasan study on base score is 7 people (38,8%) increased cycle I be II people (61,11%) increased again in the cycle of II be 17 people (94,4%) this you can deduce that if applied cooperative learning model of thpe numbered head together IPA lerarning results may increase grade IV SDN 038 Sekeladi.Keywords : cooperative learning model of type numbered head together (NHT) results learn IPA.